ROLE OF HYDROGEN PEROXIDE (H2O2) IN YOGHURT (Lactobacillus bulgaricus and Streptococcus thermophilus) IN INHIBITING THE GROWTH OF Staphylococcus epidermidis CAUSES OF ACNE VULGARIS - Peramiarti, Idsap; Setiawati, Setiawati; Williem, Williem (Medical and Health Journal, 2024)
Acne vulgaris (AV) is an inflammation of the pilosebaceous follicles caused by the bacterium Staphylococcus epidermidis (S. epidermidis). Yoghurt is the result of fermented milk with a mixture of Lactobacillus bulgaricus and Streptococcus thermophilus as Lactic Acid Bacteria (BAL) which produce several compounds like lactic acid, bacteriocin, hydrogen peroxide, and carbon dioxide. Hydrogen peroxide is effective in reducing inflammatory and non-inflammatory lesions in AV patients. This study aims to determine whether hydrogen peroxide produced by lactic acid bacteria in yoghurt affects inhibiting the growth of S. epidermidis. This research is an experimental study with the post-test only method with control group design which was conducted in vitro. Analysis of H2O2 levels in yoghurt using permanganometric titration. Bacterial growth inhibition test using macro delusion and colony counter. The samples used were 30 samples with two repetitions and divided into 10 concentration groups (0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%) with 0 % as negative control. Differences in treatment group barriers were analyzed using the One Way ANOVA test. One Way Anova test showed p < 0.001 which indicated a significant difference between each concentration group. The results of the Post-Hoc LSD test were p<0.05 between the control group and all treatment groups. H2O2 in yoghurt has antibacterial activity against S. epidermidis. This study showed that there was an inhibition of the growth of S. epidermidis by yoghurt at concentration of 5% had a hydrogen peroxide content of 0.17 mg/mL and pH of 5.7 was the minimum inhibitory concentration of S. epidermidis growth.